The adventures of huckleberry finn - Twain, Mark (Penguin Books , London, 1994)
"Someone killed Huckleberry Finn." Everyone in the village of St. Petersburg will tell you this, but Huck Finn is not dead. He ran away. Now he is traveling down the great Mississippi river. Come with him on his adventures and meet many new people. Some of them are good, but some of them are very bad." --Back cover